2023
DOI: 10.1111/cen.14933
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of 11C‐methionine PET/CT in primary hyperparathyroidism in a UK cohort: A single‐centre experience and literature review

Kevin A. Huynh,
James MacFarlane,
Christine Newman
et al.

Abstract: Objective: Primary hyperparathyroidism is a common endocrine disorder, with 80% of all cases usually caused by one single hyperfunctioning parathyroid adenoma.Conventional imaging modalities for the diagnostic work-up of primary hyperparathyroidism (PHPT) include ultrasound of the neck, 99mTc-sestamibi scintigraphy, and four-dimensional computed tomography (4D-CT). However, the role of other imaging modalities, such as 11C-methionine PET/CT, in the care pathway for PHPT is currently unclear. Here, we report ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(183 reference statements)
0
2
0
Order By: Relevance
“…Recently, 11C-methionine, 11C-choline or 18F-fluorocholine PET/CT showed encouraging outcomes, especially in patients who underwent unsuccessful parathyroidectomy or had negative or discordant imaging results pre-surgery, with these patients being alternatively candidates to SPECT/CT, as well [44][45][46][47]. Head-to-head studies (versus 99m-Tc sestamibi SPECT/CT) showed comparable results despite using a different tracer for parathyroid glands [48] or even an improvement in detection rate, for instance, from 88% for 99m-Tc-sestamibi SPECT/CT to 98% according to one recent study [49] or a sensitivity of 99% for 18F-fluorocholine PET/CT versus 75% for ultrasound versus 65% for 99m-Tc sestamibi scintigraphy versus 89.9% for ultrasound combined with this type of scintigraphy according to another cohort from 2022 [50].…”
Section: Concordance Of Pre-operatory Localisation Studies In Phpmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 11C-methionine, 11C-choline or 18F-fluorocholine PET/CT showed encouraging outcomes, especially in patients who underwent unsuccessful parathyroidectomy or had negative or discordant imaging results pre-surgery, with these patients being alternatively candidates to SPECT/CT, as well [44][45][46][47]. Head-to-head studies (versus 99m-Tc sestamibi SPECT/CT) showed comparable results despite using a different tracer for parathyroid glands [48] or even an improvement in detection rate, for instance, from 88% for 99m-Tc-sestamibi SPECT/CT to 98% according to one recent study [49] or a sensitivity of 99% for 18F-fluorocholine PET/CT versus 75% for ultrasound versus 65% for 99m-Tc sestamibi scintigraphy versus 89.9% for ultrasound combined with this type of scintigraphy according to another cohort from 2022 [50].…”
Section: Concordance Of Pre-operatory Localisation Studies In Phpmentioning
confidence: 99%
“…However, the implementation of such a protocol largely depends on each centre standards rather than being a guideline recommendation [60][61][62][63]. Overall, negative or discordant pre-operatory imaging results in PHP do not exclude a successful parathyroidectomy in the hands of a skilled surgeon [44,45].…”
Section: Concordance Of Pre-operatory Localisation Studies In Phpmentioning
confidence: 99%